CHITOSAN-BASED ANTIMICROBIAL COATING WITH PLANT-MEDIATED NANOPARTICLES FOR BIOMEDICAL AND SURFACE PROTECTION APPLICATIONS (Journal of Medical & Health Sciences Review, 2025)
This paper describes the design of an antimicrobial, eco-friendly, chitosan-based coating, which is strengthened by neem (Azadirachta indica)-mediated silver nanoparticles (AgNPs) to use as a biomedical and surface protection coating. Neem extract was used to synthesize crystalline AgNPs that were biosynthesized using a natural reducing and stabilizing agent, which was proven by UV-Vis spectroscopy, FTIR, XRD, SEM, and DLS. The nanoparticles were spherical, of moderate polydispersity and showed significant interaction with functional groups of chitosan, which allowed its easy integration into the polymer matrix. Fake chitosan-AgNP layers exhibited greater hydrophilicity, and a considerable reduction in water contact angle, and a proportional increase in the thickness of the coating as a function of nanoparticle loading. Antimicrobial tests- zone of inhibition, CFU reduction and time-kill kinetics showed that there was an evident dose-dependent increase in the activity against E. coli, S. aureus and C. albicans. Although pure chitosan exhibited moderate antimicrobial properties, the chitosan AgNPs composites recorded up to 98% CFU reduction, and total microbial inactivation rates in 6 hours and confirmed high AgNP loadings on the synergistic mechanism of membrane disruption, ROS generation, and phytochemical-mediated biocidal action. The joint performance, stability, and green synthesis pathway places these coatings as potential candidates in the progressive biomedical devices, protection surfaces, and industrial applications in need of a long-lasting and extensive-spectrum antimicrobial cover.